Determinants of adoption of quality protein maize varieties in Misrak Badewacho District, Southern Ethiopia: policy implications - Jambo, Yilma; Daka, Alemu; Nega, Berhanu (Frontiers in Nutrition, 2025)
This study aimed to identify the determinants of adoption of quality protein maize (QPM) varieties. QPM varieties are promoted as a solution to the problem of undernutrition, and their adoption is especially important in areas where maize is a nutritional staple food source. This study employed a cross-sectional design. A multistage sampling procedure was used to collect primary data from 143 sampled maize producers, which were analyzed using SPSS version 22. A binary logit model was used to identify major determinants. The results indicated that access to QPM seed, land size, on-farm income, involvement in off/non-farm activities, frequency of contact with development agents (Das), educational level of the household head, and participation of farmers on field days were statistically significant determinants of QPM variety adoption. Credit use was also a significant determinant of the adoption of QPM varieties but showed a negative influence. Therefore, this study recommends that all relevant stakeholders working at different levels in QPM production and extension pay attention to the factors that could affect farmers’ decisions to adopt QPM in the study area. Furthermore, all concerned bodies should work together to enhance the adoption of QPM varieties.